Slow Art : The experience of Looking, Sacred Images to James Turrell. - Reed, Arden (University of California Press : Oakland, California, 2017)
Hamilton, Emma; Wilde, Oscar; Wall, Jeff; Taylor-Ji-ohnson, Sam; Warhol, Andy; Serra Richard
contemplatie, esthetische ervaring, religieuze ervaring
boek